Bottomless barrel-sponge species in the Indo-Pacific? - Setiawan, Edwin; Voogd, Nicole J. De; Hooper, John N.a.; Wörheide, Gert; Erpenbeck, Dirk (Zootaxa, 2016)
The use of nuclear markers, in addition to traditional mitochondrial markers, helps to clarify hidden patterns of genetic structure in natural populations (Palumbi & Baker, 1994). This is particularly evident among demosponges that possess slow mitochondrial evolutionary rates compared to Bilateria, where nuclear intron markers can aid in the understanding of shallow level phylogenetic relationships (Shearer et al., 2002). Ideally, these nuclear markers (i) are evolutionary well-conserved across different lineages, (ii) produce amplicons holding a number of sites with sufficient variability to answer the relevant phylogenetic question, (iii) derive from single copy genes (see review in Zhang & Hewitt, 2003). A popular method to amplify intron markers uses EPIC (Exon-Primed, Intron-Crossing) primers that anneal to the more conserved flanking exon regions and subsequently bridge the intron during amplification (Palumbi & Baker, 1994).